PENGEMBANGAN KURIKULUM PENDIDIKAN AGAMA ISLAM DI MADRASAH (Studi Atas Pemikiran Muhaimin - Muhammad Irsad (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2016)
Islamic Religious Education Curriculum Development at Madrasah (Study On Thought Muhaimin).The question of how the fate of a country in the future, largely determined by the quality of future generations. The quality of the next generation is strongly influenced by how much the nation's attention to the quality of education. Meanwhile, one of many elements in education, curriculum plays an important role in determining the success or failure of a country achieve education goals. Muhaimin thinking about an alternative concept of curriculum development in Madrasah interesting to examine, in developing undertakings of Islamic education as a national educational subsystem. This research is a library research (library research), using a philosophical approach and analyzed using content analysis (content analysis). Muhaimin idea about the Madrasah curriculum development using a variety of approaches namely; approaches the subject of academic, humanistic approach, the technological approach, and the approach of social rekosntruksi. The concept of curriculum development Muhaimin, has advantages trsendiri by combining a variety of intelligence, including IQ (intelligent quotient), EQ (emotional quotient), CQ (creativity quotient) and SQ (spiritual quotient). Keywords: Muhaimin, Curriculum Development, Madrasah.